1981
DOI: 10.1215/03616878-6-2-205
|View full text |Cite
|
Sign up to set email alerts
|

The Second Public Health Revolution: A Critical Appraisal

Abstract: This paper presents a critical reaction to the Surgeon General's recent report and recommendations on American health. Entitled Healthy People, the report has been described as providing impetus for a "second public health revolution." Our analysis leaves us less than enthusiastic. We first summarize the Report, noting its heavy emphasis on lifestyle. We then compare its tenets with those of the nineteenth century public health revolution. The Report recognizes social and economic conditions as significant fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] The effectiveness of workplace health promotion programs in reducing health risks has been demonstrated in the areas of high blood pressure control14-6 and smoking cessation. [17][18][19] The evidence is more tentative in other areas of lifestyle change.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] The effectiveness of workplace health promotion programs in reducing health risks has been demonstrated in the areas of high blood pressure control14-6 and smoking cessation. [17][18][19] The evidence is more tentative in other areas of lifestyle change.…”
Section: Introductionmentioning
confidence: 99%
“…Similar sentiments were voiced by Baker (1980), who suggested that passive prevention will prove maximally effective because “such protection is totally independent of the wisdom, caution, skill, and psychological makeup of the individuals who are protected” (p. 467). According to this public health position, the focus on individual life-styles is misplaced because it requires individuals to “redeem” themselves (Neubauer & Pratt, 1981). Thus the emphasis on the individual’s active behavioral life-styles is believed to “blame the victim” for his or her deficiencies (Editorial, 1980) and diverts attention from the social engineering or structural changes necessary to achieve better health of the population.…”
Section: Public Health’s Focus On Passive Structural Interventionmentioning
confidence: 99%
“…One of the most significant changes in the subject matter of public health education is a direct consequence of the epidemiological transition, the decline in infectious diseases and subsequent rise in chronic diseases. In what is sometimes hailed as the "second revolution" in public health, 1 the transition signaled a major historic shift in the field's primary focus, from controlling the agent of disease ("germs") to addressing the role of the host in disease etiology. While scientists continued to search for the microorganisms that caused heart disease or cancer well into the 1960s and 1970s, the 1979 U.S.…”
Section: Introductionmentioning
confidence: 99%